2015
DOI: 10.5897/ajb2015.14521
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a peroxidase present in xilopodium exsudates of umbu plants (Spondias tuberosa A.)

Abstract: Umbu plants are drought resistant trees which are able to store water and several other substances into its adapted root, named xylopodium. The exsudate from xilopodium is a natural solution rich in salts, sugars and a little concentration of proteins. In this work, we report the purification of a peroxidase (POX) from umbu xilopodium exsudate by direct extraction from polyacrylamide electrophoresis gels. Umbu POX showed optimum activity at pHs around 6.0 to 7.0 and high thermal resistance after incubation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…Also, another study by Bhatti et al (2012) has shown peroxidase from Raphanus sativus to have an optimum activity at pH 4.0. The findings from this study agrees with findings of Pinto et al (2015) who observed a broad range of pH 4.5 up to 7.5 for umbu peroxidase and its activity maintained at 70% levels. The pH curve also showed a bell-like shape distribution suggesting an involvement of two amino acid residues in catalysis as reported by Pinto et al (2015).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Also, another study by Bhatti et al (2012) has shown peroxidase from Raphanus sativus to have an optimum activity at pH 4.0. The findings from this study agrees with findings of Pinto et al (2015) who observed a broad range of pH 4.5 up to 7.5 for umbu peroxidase and its activity maintained at 70% levels. The pH curve also showed a bell-like shape distribution suggesting an involvement of two amino acid residues in catalysis as reported by Pinto et al (2015).…”
Section: Discussionsupporting
confidence: 93%
“…Adefila et al (2012) reported similarly in their work that Ca 2+ and Mn 2+ were potent activators of αamylase. Pinto et al (2015) reported a stimulatory effect of Ca 2+ on peroxidase present in Xilopodium exsudates of umbu plants, with Mg 2+ having similar effect but at a lower concentration than that of Ca 2+ , whereas Mn 2+ displayed inhibitory effect. However, Pb 2+ inhibited the activity of the enzyme.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ainsi des activités inferieures ont été reportées chez d'autres plantes à savoir, le blé (Triticum aestivum ssp vulgare) dont l'activité est de 0,02 U/mg (Altin et al, 2017), le palmier (Phoenix dactylifera L.) dont l'activité spécifique est de 53,3 U/mg (Al-Senaidy et Ismael, 2011). Cependant, des activités supérieures ont été rapportées chez d'autres plantes à savoir radis (Raphanus sativus) dont l'activité spécifique est de 226 U/mg (Diao et al, 2018), Metroxylon sagu et Spondias tuberosa dont les activités spécifiques sont supérieures à 800 U/mg (Onsa et al, 2004 ;Pinto et al, 2015). L'activité spécifique des peroxydases de Daucus carota est de 109,8 U/mg.…”
Section: Discussionunclassified